Oscillatory properties and asymptotic behavior of the solutions of a class of operator-differential equations. (1994) - Bainov, D. D.; Dimitrova, M. B.
Abstract : In the present paper an operator-differential equation is investigated. Sufficient conditions for the presence of Kneser's properties are found.